Pengaruh Model Project Based Learning terhadap Keterampilan Menulis Teks Biografi Siswa Kelas X SMA Negeri 5 Medan (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The research that has been conducted titled "The Influence of Model Project Based Learning On Skills to Write Biography of Class X State High School Text" which is motivated that the low motivation and ability of students to write, especially in writing biographies. And the dominant method of lectures in the learning process. The method used is quantitative with a quae-experimental design in the form of pre-test and post-tests with a sample of 35 class X-1 and 35 students from class X-2. Data collection techniques with written tests, observations, documentation, and questionnaire. The results stated that (1) there is an increase in post-test results in the experiment class compared to the control class, (2) the average post-test value of experimental class students higher than the post-test student values, (3) The use of the media-based PjBL model has a positive impact on the biography text skills. Thus, the model Project Based Learning terbuktif is effective in improving the skills of biography text writing.